TINJAUAN YURIDIS PERJANJIAN SEWA MENYEWA BANGUNAN TOKO DALAM BENTUK TIDAK TERTULIS - Chomsyah, Siti (Fakultas Hukum Universitas Mahasaraswati Denpasar, 2017)
Shop building lease agreements may be made in written and unwritten form. Shop building lease agreement that formed an unwritten, all clauses agreed upon only verbally expressed. Unwritten shop building lease arrangements have weaknesses in the event of denial of clauses that agreed by either party resulting wanprestasi. The purpose of writing is to know the unwritten lease agreements based on the principles of the agreement and the legal efforts that can be taken due to the occurrence of wanprestasi of unwritten lease agreements shop buildings. In the discussion of unwritten shop lease agreements not in contravention of the principles of the agreement but the agreement with this model is vulnerable to the denial of the agreement clause. The denial of the agreement clause leads to wanprestasi, so that the problem needs to be solved in a non-litigation and non-litigation manner.